Amyloid Oligomer Neurotoxicity, Calcium Dysregulation, and Lipid Rafts. (9th January 2011) - Malchiodi-Albedi, Fiorella; Paradisi, Silvia; Matteucci, Andrea; Frank, Claudio; Diociaiuti, Marco
Abstract : Amyloid proteins constitute a chemically heterogeneous group of proteins, which share some biophysical and biological characteristics, the principal of which are the high propensity to acquire an incorrect folding and the tendency to aggregate. A number of diseases are associated with misfolding and aggregation of proteins, although only in some of them—most notably Alzheimer's disease (AD) and transmissible spongiform encephalopathies (TSEs)—a pathogenetic link with misfolded proteins is now widely recognized. Lipid rafts (LRs) have been involved in the pathophysiology of diseases associated with protein misfolding at several levels, including aggregation of misfolded proteins, amyloidogenic processing, and neurotoxicity. Among the pathogenic misfolded proteins, the AD-related protein amyloid β (A β ) is by far the most studied protein, and a large body of evidence has been gathered on the role played by LRs in A β pathogenicity. However, significant amount of data has also been collected for several other amyloid proteins, so that their ability to interact with LRs can be considered an additional, shared feature characterizing the amyloid protein family. In this paper, we will review the evidence on the role of LRs in the neurotoxicity of huntingtin, α -synuclein, prion protein, and calcitonin.